2006
DOI: 10.1007/s00213-006-0355-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delay to reinforcement on the choice between cocaine and food in rhesus monkeys

Abstract: This experiment demonstrates that the choice between cocaine and a non-drug or drug alternative can be modified by increasing the interval between behavior and drug injection. Overall, the results are consistent with a temporal discounting model of drug choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
51
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 36 publications
10
51
0
1
Order By: Relevance
“…Nondrug alternative reinforcers decrease drug selfadministration using either choice procedures or noncontingent direct exposure to an alternative rewarding stimulus (Carroll et al, 1989;Woolverton and Anderson, 2006). In humans, prosocial behaviors such as physical activity and engaging in high sensation experiences may be effective in reducing drug use.…”
Section: Implications For Prevention and Treatment Of Drug Abusementioning
confidence: 99%
“…Nondrug alternative reinforcers decrease drug selfadministration using either choice procedures or noncontingent direct exposure to an alternative rewarding stimulus (Carroll et al, 1989;Woolverton and Anderson, 2006). In humans, prosocial behaviors such as physical activity and engaging in high sensation experiences may be effective in reducing drug use.…”
Section: Implications For Prevention and Treatment Of Drug Abusementioning
confidence: 99%
“…Few medications have selectively and robustly shifted cocaine self-administration, but it may be that this behavior would be more sensitive to medication effects if alternative reinforcers were immediate (as the cocaine reinforcer is). For example, non-human primates responding to receive either cocaine or an alternative reinforcer chose less cocaine if the delivery of the alternative reinforcer was immediate compared to when the delivery of the alternative reinforcer was delayed (Woolverton and Anderson 2006). In most human laboratory procedures, the alternative reinforcer is not available until completion of the study.…”
Section: Alternative Reinforcersmentioning
confidence: 99%
“…For example, imposing a delay between completion of the response requirement and delivery of an infusion of cocaine decreases response rates in rhesus monkeys lever pressing under a single-response self-administration procedure (Beardsley and Balster, 1993). More recently, researchers (Anderson and Woolverton, 2003;Woolverton and Anderson, 2006;Woolverton et al, 2007) showed that delay impacts self-administration of cocaine under concurrent choice procedures. For example, when given a choice between smaller doses of cocaine delivered immediately and a large dose of cocaine delivered after a delay, rhesus monkeys responded less for the large, delayed dose and more for the smaller, immediately available doses (Woolverton and Anderson, 2006;Woolverton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers (Anderson and Woolverton, 2003;Woolverton and Anderson, 2006;Woolverton et al, 2007) showed that delay impacts self-administration of cocaine under concurrent choice procedures. For example, when given a choice between smaller doses of cocaine delivered immediately and a large dose of cocaine delivered after a delay, rhesus monkeys responded less for the large, delayed dose and more for the smaller, immediately available doses (Woolverton and Anderson, 2006;Woolverton et al, 2007). Woolverton et al (2007) further demonstrated that decreased choice of the large, delayed dose of cocaine was well described by a hyperbolic discounting function in a manner comparable to other types of reinforcers (Mazur, 1987), suggesting that choice involving drug and nondrug reinforcers is likely under the control of similar behavioral processes.…”
Section: Introductionmentioning
confidence: 99%